Existential performance of individuals with different self-relationship - Tsagelskaya, Darya E. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The article discusses results of an empirical study dedicated to the revealing differences in the existential fulfillment of individuals with different self-attitude. Existential fulfillment is a significant predictor of professional efficiency and quality of life of the population. Self-attitude as integrative characteristic has a regulatory potential, and can be considered as an indirect factor of existential fulfillment. The study revealed parameters of self-attitude more manifested in individuals with a high level of existential fulfillment. The results of the study can be used in individual counseling and socio-psychological training.